Humor v večkodnih učbeniških besedilih za slovenščino v osnovni šoli - Rodela, Martina (Revija za elementarno izobraževanje, 2023)
Research mostly establishes the benefits of humour in the learning process when used properly. We determine how primary school textbooks for Slovene as a mother tongue use verbal and pictorial semiotic resources to create humour when learning grammar, which resources are used more often, and how humour is perceived by pupils. Images are the main carrier of information in the creation of humour. An essential component of it is discrepancy with reality, most often expressed as exaggeration. For pupils aged 8 and 10, the involvement of humour is more important than for pupils aged 14.
Keywords: humor; interpersonal metafunction; medosebna metafunkcija; multimodal textbook; Slovene; slovenščina; večkodni učbenik